PERTUMBUHAN BEBERAPA JENIS LEGUMINOSA TUMBUH-CEPAT DI LAPANGAN SETELAH SEMABSfYA DIINOKULASI DENGAN RHIZOBIUM - DANIMIHARDJA, S.; SAEFUDIN, SAEFUDIN; SYARIF, F.; SETYOWATMNDARTO, N. (BERITA BIOLOGI, 1988)
S. DANIMIHARDJA,SAEFUDIN,F. SYARIF & N.SETYOWATMNDARTO. 1987. The growthof some fast-growing legume species in the field after seedling inoculation with Rhizobium.Berita Biologi 3(8): 377 - 381.Eleven species of fast growing legumes were grown in the field after their root seedlings were inoculated with two selected strains of Rhizobium sp.The results indicated that Acacia villosa was the fastest growing species (324.8 cm in height and 28.35 mm in diameter after 13 months of planting).The slowest one was Albizia procera (86.20 cm and 10.45 mm).The statistical analysis indicated that between species there were highly significant differences either in height or in diameter of the plants. Between treatments there was significant difference in diameter, but not in height.The interaction between treatments and species was highly significant difference in diameter, but not significant one in height. After 13 months of planting 6 species had already produced pods,namely Acacia villosa,Albizia lebbeck,Bauhinia acurninata, B. purpurea, Caesalpinia pulcherrima and 7 C.sappan.The death rates were ranging from 19% (in Albizia chinensis),30%(in A. falcatariaj, 46% (in A. procera),47% (in A. lebbeck), until 50% (in Acacia auriculiformis).